Protected area downgrading, downsizing, and degazettement as a threat to iconic protected areas. Issue 6 (17th July 2019) - Qin, Siyu; Golden Kroner, Rachel E.; Cook, Carly; Tesfaw, Anteneh T.; Braybrook, Rowan; Rodriguez, Carlos Manuel; Poelking, Claire; Mascia, Michael B.
Abstract: Protected areas (PAs) are expected to conserve nature and provide ecosystem services in perpetuity, yet widespread protected area downgrading, downsizing, and degazettement (PADDD) may compromise these objectives. Even iconic protected areas are vulnerable to PADDD, although these PADDD events are often unrecognized. We identified 23 enacted and proposed PADDD events within World Natural Heritage Sites and examined the history, context, and consequences of PADDD events in 4 iconic PAs (Yosemite National Park, Arabian Oryx Sanctuary, Yasuní National Park, and Virunga National Park). Based on insights from published research and international workshops, these 4 cases revealed the diverse pressures brought on by competing interests to develop or exploit natural landscapes and the variety of mechanisms that enables PADDD. Knowledge gaps exist in understanding of the conditions through which development pressures translate to PADDD events and their impacts, partially due to a lack of comprehensive PADDD records. Future research priorities should include comprehensive regional and country‐level profiles and analysis of risks, impacts, and contextual factors related to PADDD. Policy options to better govern PADDD include improving tracking and reporting of PADDD events, establishing transparent PADDD policy processes, coordinating among legal frameworks, and mitigating negative impacts of PADDD. To support PADDD research and policy reforms, enhanced human and financial capacities are needed to train local researchers and to host publicly accessible data. As the conservation community considers the achievements of Aichi Target 11 and moves toward new biodiversity targets beyond 2020, researchers, practitioners, and policy makers need to work together to better track, assess, and govern PADDD globally. Abstract : Article impact statement : Legal changes affect even iconic protected areas. Sustaining conservation progress requires research, policies, and human‐capacity investments. Abstract : Cambios de Categoría, Reducción del Tamaño y Eliminación de las Listas de Protección como Amenazas para las Áreas Protegidas Icónicas Resumen: Se espera que las áreas protegidas (PAs, en inglés) conserven la naturaleza y proporcionen servicios ambientales a perpetuidad, sin embargo las extensas prácticas de reducción del tamaño, eliminación de las listas de protección y cambios de categoría de las áreas protegidas (PADDD, en inglés) pueden poner en riesgo a estos objetivos. Incluso las áreas protegidas icónicas son vulnerables a los PADDD, aunque estos eventos de PADDD comúnmente no se reconocen. Identificamos 23 eventos de PADDDD promulgados y propuestos dentro de sitios de Patrimonio Natural Mundial y examinamos la historia, el contexto y las consecuencias de los eventos PADDD en cuatro PAs icónicas (el Parque Nacional Yosemite, el Santuario del Oryx Árabe, el Parque Nacional Yasuní y el Parque Nacional Virunga). Con base en el conocimiento obtenido de investigaciones publicadas y talleres internacionales, estos cuatro casos revelaron las diferentes presiones que traen consigo los intereses en competencia por desarrollar o explotar los paisajes naturales y la variedad de mecanismos que faciliten las PADDD. Existen vacíos de conocimiento en el entendimiento de las condiciones a través de las cuales las presiones del desarrollo se transforman en eventos PADDD y los impactos que tienen, parcialmente debido a la falta de registros completos de los eventos PADDD. Las prioridades de las próximas investigaciones deberían incluir perfiles completos a nivel regional y nacional y un análisis de riesgo, impactos y factores contextuales relacionados con los PADDD. Las opciones políticas para gobernar de mejor manera los PADDD incluyen la mejora del rastreo y del reporte de eventos PADDD, el establecimiento de procesos políticos transparentes para los PADDD, la coordinación entre los marcos de trabajo legales y la mitigación de los impactos negativos de los PADDD. Para apoyar la investigación de los PADDD y las reformas políticas se requiere de una mayor capacidad humana y financiera para entrenar a los investigadores locales y para acoger datos accesibles para el público. Conforme la comunidad de la conservación considera los logros del Objetivo 11 de Aichi y se posiciona hacia nuevos objetivos para la biodiversidad más allá del 2020, los investigadores, los practicantes y los legisladores necesitan trabajar en conjunto para rastrear, evaluar y gobernar de mejor manera los PADDD a nivel mundial. 摘要: 建立保护区 (PA) 的初衷是永久性地保护自然和提供生态系统服务, 然而广泛的保护区降级、缩减和撤销 (PADDD) 或将危及这些目标。即便是标志性的保护区也未必免于 PADDD, 尽管这些PADDD未被注意。我们确认了发生于世界自然遗产地中的 23 起 PADDD 事件, 并分析了四个标志性保护区 (优胜美地国家公园、阿拉伯羚羊保护区、亚苏尼国家公园和维龙加国家公园) 中的 PADDD 事件及其历史、背景和后果。基于已发表的研究和研讨会中的见解, 这 4 个案例进一步揭示了各种开发利用自然的压力、不同利益间的讨价还价、和实现 PADDD 的多种机制。对于在何种情况下这些开发压力会转换为 PADDD 事件并导致何种影响, 我们的理解还存在缺口, 部分原因是缺乏相对完整的 PADDD 记录。未来的研究重点应当包括建立完整的区域及国家的 PADDD 概况, 分析 PADDD 的风险、影响和相关的情景因素。更好管治 PADDD 的政策则包括优化对 PADDD 事件的记录和报告, 建立透明的 PADDD 政策流程, 协调法律框架以及减缓PADDD的负面影响。为支持 PADDD 研究和政策改进, 尚需增加人力及财力投入以培训当地研究人员和存放公众可获取的数据。随着保护界评估爱知目标 11 的成就并向 2020 年后的新生物多样性目标迈进, 研究人员、保护从业者及政策制定者需要携手合作, 以更好地在全球层面上记录、评估、和管理 PADDD。